Agrin Influences Botulinum Neurotoxin A-Induced Nerve Sprouting via miR-144-agrin-MuSK Signaling - Ma, Lin; Pan, Lizhen; Liu, Wuchao; Liu, Ying; Xiang, Xuerui; Pan, Yougui; Zhang, Xiaolong; Jin, Lingjing (Frontiers in Cell and Developmental Biology, 2020)
Botulinum neurotoxin (BoNT) has become a powerful therapeutic tool, and is extensively used in aesthetic medicine and in the treatment of neurological disorders. However, its duration of effect is limited, mainly owing to nerve sprouting. Inhibition of nerve sprouting to prolong the effective duration of BoNT is therefore of great clinical interest. However, appropriate interventional strategies to accomplish this are currently unavailable. In this study, we determined the role of the neurogenic regulator agrin in BoNT type A (BoNT/A)-induced nerve sprouting in a rat model. We then determined whether agrin could be used as an interventional target for prolonging the duration of effect of BoNT/A, and made a preliminary study of the upstream and downstream regulatory mechanisms by which agrin could influence the effective duration of BoNT/A. Our results showed that agrin was involved in the regulation of BoNT/A-induced nerve sprouting, and blocking of agrin function with anti-agrin antibody temporarily could delay muscle strength recovery and prolong the duration of BoNT/A effect. Moreover, agrin influenced the duration of BoNT/A effect by regulating downstream myogenic muscle-specific receptor tyrosine kinase (MuSK), and was simultaneously regulated by upstream miR-144. In conclusion, agrin could regulate BoNT/A-induced nerve sprouting through miR-144-agrin-MuSK signaling; it influences the effective duration of BoNT/A, and could find clinical application as a interventional target for prolonging the effect of BoNT/A.